Intestinal Damage, Inflammation and Microbiota Alteration during COVID-19 Infection - Angela Saviano; Mattia Brigida; Carmine Petruzziello; Christian Zanza; Marcello Candelli; Maria Rita Morabito Loprete; Faiz Saleem; Veronica Ojetti (Biomedicines, 2023)
Background: The virus SARS-CoV-2 is responsible for respiratory disorders due to the fact that it mainly infects the respiratory tract using the Angiotensin-converting enzyme 2 (ACE2) receptors. ACE2 receptors are also highly expressed on intestinal cells, representing an important site of entry for the virus in the gut. Literature studies underlined that the virus infects and replicates in the gut epithelial cells, causing gastrointestinal symptoms such as diarrhea, abdominal pain, nausea/vomiting and anorexia. Moreover, the SARS-CoV-2 virus settles into the bloodstream, hyperactivating the platelets and cytokine storms and causing gut–blood barrier damage with an alteration of the gut microbiota, intestinal cell injury, intestinal vessel thrombosis leading to malabsorption, malnutrition, an increasing disease severity and mortality with short and long-period sequelae. Conclusion: This review summarizes the data on how SARS-CoV-2 effects on the gastrointestinal systems, including the mechanisms of inflammation, relationship with the gut microbiota, endoscopic patterns, and the role of fecal calprotectin, confirming the importance of the digestive system in clinical practice for the diagnosis and follow-up of SARS-CoV-2 infection.